Andragogy learning and the associated factors among nursing students in online palliative class during the COVID-19 pandemic - Agustini, Ni Luh Inca Buntari; Nursalam; Sukartini, Tintin; Rismawan, Made; Yusniawati, Yustina Ni Putu; Suantika, Putu Inge Ruth (Journal of the Pakistan Medical Association, 2023)
Objective: To investigate the andragogy learning and determine the related factors among nursing students in online palliative class during the coronavirus disease-2019 pandemic. Methods: The descriptive cross-sectional online survey-based study was conducted from September 1 to December 31, 2021, after approval from the ethics review committee of the Institute of Technology and Health Bali, Indonesia, and comprised 2nd year nursing students enrolled in the online palliative class. Data was collected using a questionnaire to measure socio-demographic characteristics of the respondents, teacher characteristics, and learning media. Andragogy education movement questionnaire was used to measure students’ self-concept, learning motivation, readiness to learn, orientation to learn, and learning experience. Data was analysed using SPSS 25. Results: Of the 189 subjects, 161(85.2%) were females, and 90(47.6%) were aged 20 years, followed by 87(46%) aged 21 years, 10(5.3%) aged 22 years and 2(1.1%) aged 23 years. Age was significantly correlated with self-concepts (p=0.04), while parents’ occupation was significantly correlated with learning motivation (p=0.04). Professional ability, personal quality and interpersonal relationships of teachers and learning media, including class management and props, were correlated with andragogy learning (p<0.001). Conclusions: High levels in all domains of andragogy learning were found. Maintaining the factors that influence andragogy learning through online platforms is an important goal in today’s virtual learning era. Keywords: Demography, Nursing, Motivation, COVID-19, Technology, Andragogy.